Production and Characterization of Exopolysaccharide From Newly Isolated Marine Probiotic Lactiplantibacillus plantarum EI6 With in vitro Wound Healing Activity - Zaghloul, Eman H.; Ibrahim, Mohamed I. A. (Frontiers in Microbiology, 2022)
Exopolysaccharide (EPS) from lactic acid bacteria (LAB) was developed as a potential biopolymer due to its safety, biological activities and special characteristics. Rare studies have investigated EPS produced by marine LAB. This study reports an EPS produced by a marine isolate identified as Lactiplantibacillus plantarum EI6 for its wound healing activity. The probiotic properties of L. plantarum EI6 were assessed. It showed promising antimicrobial activity against different pathogenic bacteria, and it was able to withstand stomach pH 3, tolerate 0.3% bile salts concentration, and it showed no signs of hemolysis. Furthermore, EI6 was able to produce 270 mg/L of EPS upon growth for 48 h at 37 °C in MRS medium enriched with 1.0% sucrose. The chemical features of the novel EI6-EPS were investigated: the UV-Vis estimated a high carbohydrate content of 91.5%, and the FTIR emphasized its polysaccharide nature by the characteristic hydroxyl, amide I, II & III and glycosidic linkage regions. The GC-MS and NMR analyses suggested the existence of five monosaccharides namely rhamnose, galactose, mannose, glucose, arabinose, existing mainly in the pyranose form and linked together by α- and β-glycosidic linkages. EI6-EPS showed safety (IC50 > 100 µg/ml) and induced human skin fibroblasts (HSF) proliferation and migration. These findings imply that EI6 can be used as a safe source for bioactive polymer in wound care.